Isotropic Optical Mouse Placement for Mobile Robot Velocity Estimation. (13th June 2014) - Kim, Sungbok
This paper presents the isotropic placement of multiple optical mice for the velocity estimation of a mobile robot. It is assumed that there can be positional restriction on the installation of optical mice at the bottom of a mobile robot. First, the velocity kinematics of a mobile robot with an array of optical mice is obtained and the resulting Jacobian matrix is analysed symbolically. Second, the isotropic, anisotropic and singular optical mouse placements are identified, along with the corresponding characteristic lengths. Third, the least squares mobile robot velocity estimation from the noisy optical mouse velocity measurements is discussed. Finally, simulation results for several different placements of three optical mice are given.